Water: amplifying impact through the CGIAR Initiative on one health - Mateo-Sagasta, Javier (International Water Management Institute, 2023)
Water plays a crucial role as a key connector between the three components of One Health. What happens to water upstream affects humans and animals downstream. The concept of One Health recognizes the interconnectedness of human, animal and environment health and emphasizes the importance of addressing health challenges through a holistic approach that integrates multiple disciplines and sectors. Globally, the health of water is affected by various water users and pollution sources including cities, towns, crops, livestock and industries. Water scarcity, water pollution and inadequate water management have profound impacts on the health of people and animals and the ecosystems where they co-exist. Climate change, population growth, increased per capita consumption and unsustainable production all aggravate this challenge.